FACTORS THAT INFLUENCE PURCHASING DECISIONS ON LUXCRIME COSMETIC PRODUCTS: FACTORS THAT INFLUENCE PURCHASING DECISIONS ON LUXCRIME COSMETIC PRODUCTS - Tamara, Munir; Hartono, Hartono; Subagja, Ghia (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
The purpose of this study was to determine the influence of viral marketing and reference groups on purchasing decisions for Luxcrime products. The type of research is Explanatory Research with a quantitative approach. This research uses the Purposive Sampling method with sample calculation using the Slovin formula, thus obtaining 100 respondents. The data analysis technique uses multiple regression analysis with the IBM 25 program test tool. Based on the F test (simultaneous) shows that viral marketing and reference groups together have simultaneous influence on purchasing decisions. Partially, it shows that the viral marketing variable has a significant effect and has a positive relationship on purchasing decisions and the reference group variable has a significant effect and has a positive relationship on purchasing decisions.